2017
DOI: 10.17957/ijab/15.0465
|View full text |Cite
|
Sign up to set email alerts
|

Compost and Synthetic Fertilizer Affect Vegetative Growth and Antioxidants Activities of Moringa oleifera

Abstract: Moringa oleifera Lam, a highly valuable food commodity that has wonderful range of medicinal uses and possessing high nutritional value. A pot study was conducted to evaluate the combined effects of compost and N:P:K (21:17:17) on growth and antioxidative activities of moringa under greenhouse conditions. Compost and N:P:K fertilizers were applied separately and in combination including control (no fertilizer), 100 g Compost, 2 g NPK, 2 g+100 g (NPK+ Compost), 4 g +200 g (NPK+ Compost) and 6 g+300 g (NPK+ Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
1
1
1
Order By: Relevance
“…Turkoglu et al (2007) also stated that the low IC50 value in the antioxidant activity test reflects the high antioxidant activity in a sample. The IC50 value of the leaf extract of all drumstick accessions in this experiment was much lower than the IC50 value of drumstick leaf extract reported by Anigboro et al (2019) of 3190 µg mL -1 and Sarwar et al (2017) amounted to 831.67 µg mL -1 to 1653 µg mL -1 . It means that the antioxidant activity of drumstick leaf extracts of all accessions used in this experiment was quite high, especially Sumatra accessions.…”
Section: Discussioncontrasting
confidence: 78%
“…Turkoglu et al (2007) also stated that the low IC50 value in the antioxidant activity test reflects the high antioxidant activity in a sample. The IC50 value of the leaf extract of all drumstick accessions in this experiment was much lower than the IC50 value of drumstick leaf extract reported by Anigboro et al (2019) of 3190 µg mL -1 and Sarwar et al (2017) amounted to 831.67 µg mL -1 to 1653 µg mL -1 . It means that the antioxidant activity of drumstick leaf extracts of all accessions used in this experiment was quite high, especially Sumatra accessions.…”
Section: Discussioncontrasting
confidence: 78%
“…Por lo que la lombricomposta resultó ser el abono con mayor potencial para la producción de follaje. Mientras que Sarwar et al (2017) establecieron que dosis menores al 1% de N-P-K pueden incrementar tallos y follaje de moringa en 50% o más en un suelo franco sin fertilización.…”
Section: Resultados Y Discusiónunclassified
“…NPK fertilization had a significant effect on diameter increasing [18,14]. The NPK fertilizer provided a quick supply of macronutrients (N, P, K) to the plants as compared to compost, from which the slow release of nutrients took place [19]. However, the statistical analysis also showed that there was a significant effect on the interaction of provenance and NPK fertilization.…”
Section: Diametermentioning
confidence: 91%